2017
DOI: 10.1210/jc.2016-3960
|View full text |Cite
|
Sign up to set email alerts
|

Premature Ovarian Insufficiency: Phenotypic Characterization Within Different Etiologies

Abstract: Our results regarding distinct phenotypic characteristics and association with different etiologies further confirmed the high heterogeneity of POI. Additional longitudinal clinical studies and pathogenesis research are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
67
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 34 publications
4
67
0
1
Order By: Relevance
“…POI poses a considerable risk to female reproductive health [ 1 , 2 ]. As a principal factor in female infertility, POI is diagnosed and characterized by oligomenorrhea or amenorrhea for at least four months prior to 40 years of age, and POI patients exhibit increased levels of FSH (> 25 U/L between two detections) [ 3 , 4 ]. These changes may lead to increased risk of osteoporosis, emotional issues or cardiovascular diseases; ~1% of woman worldwide are affected by POI, and etiological and pathophysiological mechanisms underlying its development have yet not been fully known [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…POI poses a considerable risk to female reproductive health [ 1 , 2 ]. As a principal factor in female infertility, POI is diagnosed and characterized by oligomenorrhea or amenorrhea for at least four months prior to 40 years of age, and POI patients exhibit increased levels of FSH (> 25 U/L between two detections) [ 3 , 4 ]. These changes may lead to increased risk of osteoporosis, emotional issues or cardiovascular diseases; ~1% of woman worldwide are affected by POI, and etiological and pathophysiological mechanisms underlying its development have yet not been fully known [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…POI is one of the most common reproductive disorders. It has been reported that the incidence of POI is approximately 1% in fertile women and is associated with immune factors in 30% of cases (Jiao et al, 2017). The complex and varied etiologies of POI have resulted in a lack of effective treatment (Laven, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al, 2017;Jagarlamudi, Reddy, Adhikari, & Liu, 2011). In recent years, according to some study results, autoimmunity is responsible for ∼4-30% of POI cases (Ebrahimi & Akbari Asbagh, 2015;Jiao et al, 2017).…”
mentioning
confidence: 99%
“…[ 5 7 ] In China, however, the frequency of pathogenic gene mutations in POI patients is generally <2%, although clinical diagnostic reports concerning these values are limited. [ 8 ] Common iatrogenic factors include surgery, radiotherapy, and chemotherapy. [ 9 ] Besides, Some POI patients have autoimmune diseases, and it is most related to autoimmune thyroid disease.…”
Section: Introductionmentioning
confidence: 99%